2017
DOI: 10.1016/j.bbadis.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of prion-like transfer in Huntington's disease models

Abstract: Most neurodegenerative diseases such as Alzheimer's, Parkinson's and Huntington's disease are hallmarked by aggregate formation of disease-related proteins. In various of these diseases transfer of aggregation-prone proteins between neurons and between neurons and glial cells has been shown, thereby initiating aggregation in neighboring cells and so propagating the disease phenotype. Whereas this prion-like transfer is well studied in Alzheimer's and Parkinson's disease, only a few studies have addressed this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Aggregative tendency, and thereby disease progression, are related to the length of the repeat. Mutant Htt (mHtt) fragments as well as polyQ peptides were also shown, upon uptake, to seed conversion of a soluble Htt reporter in cells ( Jansen et al, 2017 ).…”
Section: The Prion-like Nature Of Ndsmentioning
confidence: 99%
“…Aggregative tendency, and thereby disease progression, are related to the length of the repeat. Mutant Htt (mHtt) fragments as well as polyQ peptides were also shown, upon uptake, to seed conversion of a soluble Htt reporter in cells ( Jansen et al, 2017 ).…”
Section: The Prion-like Nature Of Ndsmentioning
confidence: 99%
“…The spatial distribution of diffusion over time in the brain networks when each of the 82 brain regions are used as starting point of diffusion. However, a number of previous studies have demonstrated that the neurobiological mechanisms underlying trans-neuronal spread is an active process, which may involve synaptic vesicles (seeJansen et al, 2017 for a review). Y-axis shows the correlation values (Pearsons correlation) and x-axis shows time in number of years.…”
mentioning
confidence: 99%
“…The network diffusion, used in the current study, models the distribution of pathology in HD as a linear passive diffusion process. However, a number of previous studies have demonstrated that the neurobiological mechanisms underlying trans-neuronal spread is an active process, which may involve synaptic vesicles (seeJansen et al, 2017 for a review). Hence, nonlinear active models will be necessary to better capture the neurobiological mechanisms of the disease spread in HD.…”
mentioning
confidence: 99%
“…In recent years, there is accumulating evidence that prionlike propagation of pathogenic proteins from cell-tocell accounts for the progression of pathology in HD and α-synucleinopathies. These prion-like spreading and seeding capacities of pathogenic mHtt and a-Syn (either neuron-to neuron or neuron-to-glia) occur via several mechanisms, including exosomal transfer, synaptic transmission, and glial phagocytosis (47)(48)(49)(50)(51)(52)(53)(54). Cell-to-cell transfer of pathogenic proteins disturbs neuroimmune network, leading to enhanced immune response and inflammation, as in these incurable neurodegenerative proteinopathies.…”
Section: Introductionmentioning
confidence: 99%